Immune Response of White Shrimp (Litopenaeus vannamei) to Different Density and IMNV Challenge - Nur Komariah Baladrat; Moch Nurhudah; Heny Budi Utari (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight Research • White shrimp (Litopenaeus vannamei) challenged with IMNV and different stocking densities • The water quality parameter values are getting worse along with the increase in stocking density • White shrimp THC value decreased with increasing stocking density and IMNV challenge test • The development of the IMNV increased with an increase in stocking density seen from the speed and percentage of the appearance of the clinical symptoms and histopathology results